A REVIEW ON DNYANENDRIYA (SENSE ORGANS) W.S.R. GHRANENDRIYA KRIYA SHARIR - Tiwari Avinash Keenu; Shilwant A. Aniket (International Journal of Ayurveda and Pharma Research, 2020)
According to Ayurveda classic texts Indriyas (Sense organ) are the apparatus to attain knowledge for Atma. These are the tools for obtaining knowledge. Acharya Charaka described Indriya as basic instrument in differentiating the living and non-living matters. Whereas in contemporary science Indriyas are dealt only with structure i.e., sense organ where the actual transduction process takes place. Indriyas are composed of five elements still specific Mahabhuta dominates precise Indriya. This is the reason behind reception of specific sensation by its respective Indriya. E.g. Prithvi Mahabhuta dominates Ghranendriya and receive knowledge of Gandha. Considering the above said, present paper focuses upon understanding of Dnyanendriya w.s.r. Ghranendriya. Adhisthana of Ghranendriya is Nasa (Nose) inside Sharir which is embedded with dominance of Prithivi Mahabhuta and is responsible for acquisition of special attribute- Gandha (smell). Regarding examination of Indriya the Dnyanendriya is examined for its functional status as the status of perfection in perception of knowledge of respective object. According to contemporary science there are about 10 to 20 million of olfactory receptor cells present in human body. The olfactory receptor is a bipolar neuron which is supported by sustentacular cells. Olfactory receptors are situated in olfactory mucus membrane. This mucus membrane contains Bowman glands. Our study reveals that concept of Acharyas in relation to Dnyanendriya as important tool to gain specific knowledge seems true even in present era. It can be opined that Ayurveda concept related to Indriya needs to be explored through research to provide evidence based information related to Indriya Sharir.